Concurrent validity and reliability of three ultra-portable vertical jump assessment technologies - Watkins, C. M.; Maunder, E.; van den Tillaar, R.; Oranchuk, D. J. (Sensors, 2020)
Vertical jump is a valuable training, testing, and readiness monitoring tool used across a multitude of sport settings. However, accurate field analysis has not always been readily available or affordable. For this study, two-dimensional motion capture (Mo-Cap), G-Flight micro-sensor, and PUSH accelerometer technologies were compared to a research-grade force-plate. Twelve healthy university students (7 males, 5 females) volunteered for this study. Each participant performed squat jumps, countermovement jumps, and drop jumps on three separate occasions. Between-device differences were determined using a one-way repeated measures ANOVA. Systematic bias was determined by limits of agreement using Bland-Altman analysis. Variability was examined via the coefficient of variation, interclass correlation coefficient, and typical error of measure. Dependent variables included jump height, contact-time, and reactive strength index (RSI). Mo-Cap held the greatest statistical similarity to force-plates, only overestimating contact-time (+12 ms). G-Flight (+1.3-4 cm) and PUSH (+4.1-4.5 cm) consistently overestimate jump height, while PUSH underestimates contact-time (-24 ms). Correspondingly, RSI was the most valid metric across all technologies. All technologies held small to moderate variably; however, variability was greatest with the G-Flight. While all technologies are practically implementable, practitioners may want to consider budget, athlete characteristics, exercise demands, set-up, and processing time before purchasing the most appropriate equipment.